A clinical perspective on endovascular stroke treatment biomechanics. (11th October 2021) - Ospel, Johanna M.; van der Lugt, Aad; Gounis, Matthew; Goyal, Mayank; Majoie, Charles B.L.M.
Abstract: Acute ischemic stroke (AIS) is caused by blockage of an arterial blood vessel in the brain by a thrombus, which interrupts oxygen supply to the brain parenchyma. The goal of endovascular stroke treatment (mechanical thrombectomy) is to restore blood flow as quickly and completely as possible. There are numerous factors that influence endovascular treatment success. They can be broadly grouped into a) factors related to blood vessels, b) factors related to the thrombus, c) factors related to endovascular treatment technique and tools and d) operator-related factors. While blood vessel and tgthro thrombus-related factors are mostly non-modifiable in the acute setting, operator and technique-related factors can be modified, and extensive research is currently being done to investigate the complex interplay of all these variables, and to optimize the modifiable factors to the maximum possible extent. In this review, we will describe these factors and how they interact with each other in detail, and outline some of their practical implications. We will conclude with a short summary and outlook on future directions for optimizing endovascular treatment success.